Metastatic recurrence after complete resection of colorectal liver metastases: impact of surgery and chemotherapy on survival - Homayounfar, K. (Springer Berlin Heidelberg, 2013)
PURPOSE: Surgery is the standard of care for resectable colorectal liver metastases (CRC-LM). Unfortunately, 60 % of patients develop secondary metastatic recurrence (SMR) after R0-resection of CRC-LM. We investigated the impact of surgical re-intervention and chemotherapy (Ctx) on survival in a consecutive series of patients with SMR. METHODS: From 01/2001 to 11/2011, 104 out of 178 consecutive patients with R0-resection of CRC-LM developed SMR and were evaluated. The impact of surgical and Ctx re-interventions on recurrence free (RFS) and cancer-specific survival (CSS) was analyzed. Median follow-up was 28.0 (95 %CI: 19.4–37.4) months. RESULTS: SMR occurred in 81 patients at a single site (49× liver, 18× lung, 14× other) and in 23 patients at multiple sites. Forty-two patients were scheduled for primary surgery. Fifty-three patients were classified as non-resectable and treated with median 5.0 [IQR, 3.0–10.0] cycles of Ctx, combined with an EGFR/VEGF-antibody in 27 patients. Nine patients received best supportive care only. R0/R1 resection could be achieved in 35 patients primarily and even in 8 patients secondarily after Ctx. Surgical morbidity and mortality were 16 and 0 %, respectively. The 5-year RFS rates for patients with R0 versus R1-resection were 22 and 24 % (p = 0.948). The 5-year CSS rate for R0/R1-resected patients was 38 % versus 10 % for those patients treated by Ctx alone (p < 0.001). CONCLUSION: In SMR, surgical re-intervention is feasible and safe in a remarkable number of patients and offers significantly longer CSS compared to patients without resection.